Impact of a new dedicated sheath device for tissue sampling of biliary stricture on pathological diagnostic yield: Retrospective study - Niiya, Fumitaka; Ishiwatari, Hirotoshi; Sasaki, Keiko; Ishikawa, Kazuma; Sato, Junya; Kishida, Yoshihiro; Imai, Kenichiro; Hotta, Kinichi; Ono, Hiroyuki (Endoscopy International Open, 2024)
Background and study aims Endoscopic transpapillary biliary forceps biopsy (TBFB) is a common method for obtaining specimens from biliary lesions. Its diagnostic yield is unsatisfactory; to overcome this disadvantage, a dedicated sheath has been developed. This study aimed to evaluate the outcomes of conventional TBFB and TBFB with a novel sheath device.Patients and methods Consecutive patients who underwent TBFB between January 2020 and December 2021 were retrospectively evaluated. The rate of obtaining adequate samples, failed attempts at forceps insertion into the bile duct, and sensitivity were compared between the two groups.Results Ninety-two patients who underwent 115 endoscopic retrograde cholangiopancreatographies (76 in the conventional group vs. 39 in the dedicated sheath group) were included. The rates of obtaining adequate samples, failed attempts of the forceps into the bile duct, and sensitivity were 72.4% vs. 89.7% (P = 0.03), 28.3% vs. 0% (P < 0.01), and 66.7% vs. 88.9% (P = 0.02), respectively.Conclusions TBFB with the novel sheath device contributed to improved sensitivity for diagnosis of biliary stricture without insertion of forceps outside the bile duct.
Keywords: Strictures; ERC topics; Pancreatobiliary (ERCP/PTCD); Diagnostic ERC